2019
DOI: 10.1186/s42834-019-0036-1
|View full text |Cite
|
Sign up to set email alerts
|

Biological wastewater treatment and bioreactor design: a review

Abstract: Various processes that have been successfully developed for wastewater treatment (treatment of industrial wastes/ effluents) have been surveyed with special reference to biological treatment including design of bioreactors. Limitations of each process, design and performance characteristics of different kinds of bioreactors developed starting from stirred tanks to packed bed, fluidized bed, moving bed, semifluidized bed, inverse fluidized bed, sludge bed/sludge blanket and downflow stationary fixed film biorea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(48 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…According to the change of slopes in this graph, it was possible to distinguish three different regions or phases. (i) First phase (i.e., Days 1–16): microorganisms took 16 days of start‐up to adapt to the new habitat [ 37,38 ] ; (ii) second phase (i.e., Days 17–24): microorganisms in both bioreactors were attracted by a high concentration of fresh feed and could efficiently biodegrade organic materials; (iii) third phase (i.e., Days 25–46): microorganisms in both bioreactors started to immobilize in the support media and formed biofilms, which gradually led to the VSS drop in the suspension part. Reduced amount of VSS in the suspension and the fact that biofilm in the support media was not mature by that time decreased microorganisms' organic decomposing efficiency in this phase; and (iv) fourth phase (i.e., Days 47 to end): starting from Day 47, the sCOD removal efficiency started to recover in the bioreactor containing Foam NaCl,80 .…”
Section: Resultsmentioning
confidence: 99%
“…According to the change of slopes in this graph, it was possible to distinguish three different regions or phases. (i) First phase (i.e., Days 1–16): microorganisms took 16 days of start‐up to adapt to the new habitat [ 37,38 ] ; (ii) second phase (i.e., Days 17–24): microorganisms in both bioreactors were attracted by a high concentration of fresh feed and could efficiently biodegrade organic materials; (iii) third phase (i.e., Days 25–46): microorganisms in both bioreactors started to immobilize in the support media and formed biofilms, which gradually led to the VSS drop in the suspension part. Reduced amount of VSS in the suspension and the fact that biofilm in the support media was not mature by that time decreased microorganisms' organic decomposing efficiency in this phase; and (iv) fourth phase (i.e., Days 47 to end): starting from Day 47, the sCOD removal efficiency started to recover in the bioreactor containing Foam NaCl,80 .…”
Section: Resultsmentioning
confidence: 99%
“…As compared with most of the physiochemical techniques, biological treatments were reported to be far more superior and well‐suited technique for remediation of inorganic and organic pollution (Lefebvre & Moletta, 2007). In addition, advanced biological methods served as a better substitute for the treatment of industrial and saline effluents (El‐Sheekh et al, 2014; Narayanan & Narayan, 2019; Semenova et al, 2013). It was also peculiarly identified that due to enormous inorganic load in saline wastewater, stand‐alone activated process is not sufficient and, therefore, bio‐augmented system consisting of salt‐tolerant organism and biofilms should be used to improvise the working efficiency of conventional activated sludge process (G. Wu et al, 2008).…”
Section: Biological Treatment Technologiesmentioning
confidence: 99%
“…A POME treatment system based on membrane technology shows high potential for eliminating the environmental problem, and in addition, this alternative treatment system offers water recycling [7]. The treated effluent has a high quality and crystal-clear water that can be used as the boiler feed water or as the source of drinking water production [8].…”
Section: Introductionmentioning
confidence: 99%